2020
DOI: 10.31367/2079-8725-2020-68-2-23-28
|View full text |Cite
|
Sign up to set email alerts
|

Radio Sensitivity of the winter and spring barley varieties according to the morphological efect of low-dose gamma irradiation on the original seeds.

Abstract: Barley is the main forage crop in the Russian Federation. Barley grain is also used for food and brewery (Filippov, 2013). It is common knowledge that low doses of gamma irradiation can have a stimulating effect on the growth and development of plants, in particular barley. However, there is a lack of knowledge about the molecular pathways responsible for the formation of the stimulation effect after low-dose seed irradiation. The use of varieties with different radio sensitivity to low-dose gamma irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Many studies have been carried out to evidence the effects of different doses of γ-irradiation on growth and yield attributes (Jan et al, 2012;Rawat et al, 2019;Kazakova et al, 2020;Volkova et al, 2020). In our study the inhibition of growth induced by high-dose irradiation is probably attributed to the cell cycle arrest during somatic cell division and/or varying damage to the entire genome (Preuss and Britt, 2003;Jan et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been carried out to evidence the effects of different doses of γ-irradiation on growth and yield attributes (Jan et al, 2012;Rawat et al, 2019;Kazakova et al, 2020;Volkova et al, 2020). In our study the inhibition of growth induced by high-dose irradiation is probably attributed to the cell cycle arrest during somatic cell division and/or varying damage to the entire genome (Preuss and Britt, 2003;Jan et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…There are different results and conclusion on the effect of seed radiation on germination rate and pattern reported by various similar studies worldwide. For example, Kazakova et al (2020) and Volkova et al (2020) found no significant differences between 0 and 20Gy treatments in pretreatment of barley seeds, while the length and weights of 100 Gy-treated roots and shoots were significantly lower than in the control. In our study all doses, including the least dose of radiation ( 50Gy) showed statistically significant difference compared with the control.…”
Section: Germination Valuementioning
confidence: 95%